KARAKTERISASI DAN PEMERIKSAAN FITOKIMIA DARI SIMPLISIA DAUN ANGGREK MERPATI (Dendrobium crumenatum Sw.) - Yudha Putra, Diky Okta; Syamsurizal, Syamsurizal; Elisma, Elisma (Acta Pharmaceutica Indonesia, 2025)
This study examined the characterization of crude drugs made from pigeon orchid leaves (Dendrobium crumenatum Sw.) and conducted phytochemical screening to identify the secondary metabolites present in them. Medicinal plants, particularly those from the orchid family, have significant potential for developing modern therapies due to the wide range of pharmacological compounds they contain, including anthocyanins, bibenzyl derivatives, and the main bioactive compound, dendrobine. In addition to their beauty, orchids are also beneficial for treating various diseases, making them a potential option for pharmaceutical preparations. The characterization results for the crude drugs derived from pigeon orchid leaves indicated water extractable matter of 42.01% and  ethanol extractable matter of 79.11%. The moisture content was measured at 16.04%, and a total ash content of 22.10%. Phytochemical screening showed the presence of alkaloids, phenolic compounds, flavonoids, saponins, and tannins in the pigeon orchid leaves, while no steroids were detected.